Lateral Meniscus Allograft Transplantation: An All-Soft Tissue All-Inside Technique - Sachin Tapasvi, M.S., D.N.B., F.R.C.S.; Anshu Shekhar, M.S.; Amit Meena, M.S., D.N.B.; Jorge Chahla, M.D., Ph.D. (Arthroscopy Techniques)
Lateral meniscus tears are common injuries encountered in association with acute anterior cruciate ligament tears. Although most tears can be repaired, some must be resected if deemed irreparable. Such patients who have undergone a subtotal lateral meniscectomy in the past are at an increased risk of developing osteoarthritis. A lateral meniscus allograft transplant (LMAT) is a treatment option that allows treating the symptoms of a meniscal-deficient knee with the potential for improved joint longevity. The various techniques of an LMAT include using a bone trough, bone plugs at the roots, or a soft tissue graft. All of these techniques have produced equivalent clinical-radiologic results. The peripheral capsular suturing of the LMAT can be performed using any of the meniscus suturing techniques. An all-inside suturing of all areas of the allograft can be accomplished when a flexible all-inside repair device is used. This makes the procedure faster and eliminates the need for a “safety incision.” The technique described here employs an all-soft tissue lateral meniscus allograft, which is repaired at the roots via transtibial tunnels and peripheries using a flexible all-inside device. No specialized equipment or extra incisions are required, and the procedure can be performed rapidly and safely.